Posted by **Anonymous** on Monday, January 16, 2012 at 12:52am.

1. Given the function f defined by f(x) = x^3-x^2-4X+4

a. Find the zeros of f

b. Write an equation of the line tangent to the graph of f at x = -1

c. The point (a, b) is on the graph of f and the line tangent to the graph at (a, b) passes through the point (0, -8) which is not on the graph of f. Find the values of a and b.

I'm positive I can do a and b, but what about c?

- Calculus -
**Mgraph**, Monday, January 16, 2012 at 2:16am
a)f(x)=(x+2)(x-1)(x-2)

c)From the graph a>=2, b>=0.

The equation of the tangent

y=b+(3a^2-2a-4)(x-a) and if x=0

y=b-(3a^3-2a^2-4a) or

y=a^3-a^2-4a+4-(3a^3-2a^2-4a)

y=-2a^3+a^2+4=(2-a)(6+3a+2a^2)-8

If a>2 then y<-8

(a,b)=(2,0)

- c) --- Calculus -
**Reiny**, Monday, January 16, 2012 at 9:58am
inherently the same as Mgraph's, but presented in slightly different way

dy/dx = f'(x) = 3x^2 - 2x - 4

at (a,b)

dy/dx = 3a^2 - 2a-4 , which is the slope of the tangent at (a,b)

but the slope of the tangent passing through (a,b) and (0,-8) is also

= (b+8)(a-0) = (b+8)/a

so (b+8)/a = 3a^2 - 2a - 4

b+8 = 3a^3 - 2a^2 - 4a

b = 3a^3 - 2a^2 - 4a - 8

but b = a^3 - a^2 + 4a + 4

3a^3 - 2a^2 - 4a - 8 = a^3 - a^2 + 4a + 4

2a^3 - a^2 - 8a - 4 = 0

a^2(a-2) - 4(a-2) = 0

(a-2)(a^2 - 4) = 0

(a-2)(a-2)(a+2) = 0

a = 2 or a = -2

but from a = -2 we cannot have a tangent to (0,-8)

so if

a = 2, then b = 8 - 4 - 8 + 4 = 0

(a,b) = (2,0)

## Answer This Question

## Related Questions

- calculus - 5. Let f be the function given by f(x) = x3- 7x + 6. a. Find the ...
- Math- calculus - Given f(x) = x ^ 3 - x ^ 2 -4x +4 Find the zeros of f. Write an...
- Calculus - Functions? - #1. A cubic polynomial function f is defined by f(x) = ...
- calculous - 3.Given the function f defined by f(x)=2x^3-3x^2-12x+20 a.Find the ...
- Calculus - Given the function defined as f(x)=x^3-(3/2)x^2-6x+10 a) Explain why ...
- Calculus - Given the function defined as f(x)=x^3-(3/2)x^2-6x+10 a) Explain why ...
- Calculus - The function g is defined for x>0 with g(1)=2, g'(x)=sin(x+1/x), ...
- Calculus - Let f be the function defined by f(x)=2x+11-3e^x If the equation of ...
- Calculus - 1. a) For the Function and point below , Find f’(a). b) Determine ...
- Calculus - 1. a) For the Function and point below , Find f’(a). b) Determine ...

More Related Questions